The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1540-5850.2011.00990.x
|View full text |Cite
|
Sign up to set email alerts
|

Mexican Municipalities and the Flypaper Effect

Abstract: We investigate the phenomenon of flypaper effect and its relationship with the local tax effort by using a panel data comprising approximately 48 percent of the Mexican municipalities. Our estimations based on the fixed effect and difference GMM estimators confirm the existence of flypaper effect. Moreover, we find evidence to suggest that the richer municipalities are likely to experience substitution effect, i.e., the lower levels of tax effort. We also find that the magnitude of the flypaper effect is a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 8 publications
0
7
0
3
Order By: Relevance
“…Concerning the utility function, empirical studies generally use municipalities' socio‐economic characteristics as a proxy for the preferences of the median voter (Mendes and Sampaio ; Nesbit and Kreft ; Cardenas and Sharma ). To control the effects of municipalities' socio‐economic characteristics, we have taken into account population size, age structure, and unemployment rate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the utility function, empirical studies generally use municipalities' socio‐economic characteristics as a proxy for the preferences of the median voter (Mendes and Sampaio ; Nesbit and Kreft ; Cardenas and Sharma ). To control the effects of municipalities' socio‐economic characteristics, we have taken into account population size, age structure, and unemployment rate.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that the effect of unconditional grants on local governments' expenditures is greater than the effect of the median voter income (Heyndels ; Gamkhar ; Levaggi and Zanola ; Deller and Maher ; Brooks and Phillips ; Lago‐Peñas ; Nesbit and Kreft ; Acosta ; Cardenas and Sharma ). This anomaly, known as the flypaper effect, has led to considerable research attempting to understand the gap between the predictions of the classic theory of public finance and the findings of empirical studies.…”
Section: Study Backgroundmentioning
confidence: 99%
“…The second specification test involves a Sargan test of exogeneity of instruments, which basically tests the null hypothesis of overall validity of the instruments. Failure to reject this null hypothesis ratifies the validity of instruments (see, for example, Cárdenas and Sharma, 2011;Dutt, 2009;Fajnzylber, Lederman and Loayza, 2002;Sharma, 2015). 4 Thus, we estimate the transformed equation, which is obtained by taking the first differences:…”
Section: Econometric Strategymentioning
confidence: 99%
“…La segunda prueba de la especificación es una prueba de Sargan sobre la exogeneidad de los instrumentos, que esencialmente examina la hipótesis nula de validez general de los instrumentos. Si no se rechaza esta hipótesis nula se ratifica la validez de los instrumentos (véase, por ejemplo, Cárdenas y Sharma, 2011;Dutt, 2009;Fajnzylber, Lederman y Loayza, 2002;y Sharma, 2015)…”
Section: Estrategia Econométricaunclassified